2017
DOI: 10.1145/3054912
|View full text |Cite
|
Sign up to set email alerts
|

Imitation Learning

Abstract: Imitation learning techniques aim to mimic human behavior in a given task. An agent (a learning machine) is trained to perform a task from demonstrations by learning a mapping between observations and actions. The idea of teaching by imitation has been around for many years; however, the field is gaining attention recently due to advances in computing and sensing as well as rising demand for intelligent applications. The paradigm of learning by imitation is gaining popularity because it facilitates teaching co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
154
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 702 publications
(156 citation statements)
references
References 102 publications
(90 reference statements)
1
154
0
1
Order By: Relevance
“…Employing human demon strations, a robot is trained to perform a task by learning a mapping between observations and actions. 8 Demonstra tions in connections with virtual reality and motion capture permit the efficient and scalable recording of demonstration data. Having an experienced human operator provide good examples to learn from speeds up the process of learning for a performant model.…”
Section: Learning Methodsmentioning
confidence: 99%
“…Employing human demon strations, a robot is trained to perform a task by learning a mapping between observations and actions. 8 Demonstra tions in connections with virtual reality and motion capture permit the efficient and scalable recording of demonstration data. Having an experienced human operator provide good examples to learn from speeds up the process of learning for a performant model.…”
Section: Learning Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the problem of robots in performing a task in the presence of stationary [181]- [183] or moving obstacles, which are regarded as a special consideration during demonstrations [184]. On the contrary, applying motion planning and task programming is considered a solution for avoiding the complexity of manual programming, and it can be provided by the LfD approach [185].…”
Section: Robots Learning From Demonstrationmentioning
confidence: 99%
“…It discussed fine-grained sentiment analysis and algorithm classification. [24] To depict the n-gram, unigram, and focuses on interpreting the sentiment in every single sentence.…”
Section: Reference Numbermentioning
confidence: 99%